RNA-binding protein gene NOP58 exhibits crucial prognostic and therapeutic value in Ewing sarcoma - Yannan Geng; Lu Yang; Rui Shao; Tiantong Xu; Lilong Zhang (Hereditas)
Abstract Background Our aim was to identify crucial RNA-binding proteins (RBP) genes associated with Ewing sarcoma (EwS) in order to provide valuable insights into its mechanisms of tumorigenesis and to enhance therapeutic intervention. Results Differential gene expression analysis identified candidate genes. Next, hub genes were generated by the results of protein-protein interaction (PPI) network, and univariate COX regression analysis. CIBERSORT was applied to analyze immune landscape. Furthermore, both in vitro and in vivo experiments were conducted to investigate the function of NOP58 in EwS. Results A total of 179 RBP-related genes were significantly different in EwS tissues and normal controls. Among these, NOP58 ribonucleoprotein (NOP58) was considered as the hub gene, demonstrating significant prognostic value. Significantly, high NOP58 expression correlated with poor prognosis of EwS patients. Additionally, the levels of NOP58 were significantly up-regulated in EwS cells compared with human mesenchymal stem cells. Furthermore, knockdown of NOP58 notably inhibited the proliferation and migration of EwS cells. Moreover, NOP58 deficiency remarkably induced apoptosis and cell cycle arrest in EwS cells. In vivo studies on tumor-bearing mice demonstrated that NOP58 downregulation significantly inhibited tumor growth in EwS. Conclusion Collectively, downregulation of NOP58 could inhibit the proliferation and migration of EwS cells in vitro and reduce murine xenograft tumor growth in vivo. These findings identified NOP58 as a promising regulator of EwS tumorigenesis, suggesting it may serve as a potential therapeutic target for EwS treatment.